Assessing Accountability in BPJS Services at Ciamis District Hospital, West Java: A Critical Analysis - Maria Lusiana F Werang; Grice Ine (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This research investigates the dimensions of public accountability related to the services of the Social Security Administering Agency (BPJS) at the Ciamis District Hospital, West Java, by applying a descriptive qualitative approach and desk study methods. Then, data was collected through news sources and related documents to understand the context of BPJS health services from the government and community perspective. The research results highlight non-optimal accountability in health services as the main problem, which requires strengthening the controlling function by RSUD through steps such as audits and inspections to ensure compliance with service standards. Then, efforts to increase transparency and community participation are also considered fundamental by taking initiatives to socialize participants' rights and obligations and establishing participation forums. Finally, government firmness is needed in determining sanctions and incentives for RSUDs that do not comply with regulations by ensuring strict supervision during the implementation of BPJS services. In conclusion, this research emphasizes the urgency of understanding public accountability in the BPJS health service dimension, with an emphasis on the role of the government and the Ciamis District Hospital in the perspective of vertical and horizontal accountability.